Application of the Recitation Method in Arabic Subjects in Online Learning at Baiturrohman Elementary School - Yusiana Yusiana; Indah Farida (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Jember, 2022)
To prevent the spread of COVID-19, the government has issued a learning policy to be carried out online (online). As implemented at Baiturrohman Elementary School, online learning is applied. This research uses a qualitative approach, and the type is a case study. Data collection techniques used participatory observation, structured interviews, and documentation—data analysis using data condensation, data presentation, and concluding. The validity of the data is source triangulation and technical triangulation. The results of this study indicate: (1) Planning the Recitation Method for Arabic Language Subjects in Online Learning at Baiturrohman Elementary School, namely: The teacher determines the goals according to the lesson plans, gives assignments according to the student's abilities, determines the types of assignments such as reading, writing, and practice. Provide instructions/resources in student books and several applications. The teacher provides time for the deadline for submitting assignments from 07.30 to 18.00 in Google Classroom. (2) Implementation of the Recitation Method on Arabic Language Subjects in Online Learning at Baiturrohman Elementary School, namely: Teachers provide guidance if they have difficulties, provide motivation to study at home, and support parents for children's learning at home; students do assignments at home independently. independent. (3) Evaluation of the Recitation Method on Arabic Subjects in Online Learning at Baiturrohman Elementary School, namely: Student assignments are written in spoken/written packages, sent in the form of photos/videos via Google Classroom, Teacher assessments via Google Classroom, Result assessment PH is done via a google form. Dalam upaya mencegah penyebaran covid-19, pemerintah telah mengeluarkan kebijakan pembelajaran dilaksanakan secara dalam jaringan (daring), sebagaimana yang diterapkan di SD Baiturrohman diterapkan pembelajaran dalam jaringan (daring). Penelitian ini menggunakan pendekatan kualitatif dan jenisnya studi kasus. Teknik pengumpulan data menggunakan observasi partisipasif, wawancara terstruktur dan dokumentasi. Analisis data menggunakan kondensasi data, penyajian data, penarikan kesimpulan. Keabsahan datanya triangulasi sumber dan triangulasi teknik. Hasil penelitian ini menunjukkan: (1) Perencanaan Metode Resitasi Pada Mata Pelajaran Bahasa Arab Dalam Pembelajaran Daring di Sekolah Dasar Baiturrohman yaitu: Guru menentukan tujuan sesuai RPP, memberikan tugas sesuai kemampuan siswa, menentukan jenis tugas seperti membaca, menulis dan praktek. Memberikan petunjuk/ sumber dibuku siswa dan beberapa aplikasi. Guru menyediakan waktu untuk batas pengumpulan tugasdari jam 07.30 sampai 18.00 di google classroom. (2) Pelaksanaan Metode Resitasi Pada Mata Pelajaran Bahasa Arab Dalam Pembelajaran Daring di Sekolah Dasar Baiturrohman, yaitu: Guru memberikan bimbingan jika mengalami kesulitan, memberikan motivasi semangat belajar di rumah dan pendampingan orang tua terhadap pembelajaran anak di rumah, peserta didik mengerjakan tugas dirumah secara mandiri. (3) Evaluasi Metode Resitasi Pada Mata Pelajaran Bahasa Arab Dalam Pembelajaran Daring di Sekolah Dasar Baiturrohman, yaitu: Tugas peserta didik dibuku paket berbentuk lisan/ tertulis, dikirim dalam bentuk di foto/video melalui google classroom, Penilaian guru melalui google clasroom, penilaian hasil PH dilakukan melalui google form.